Effects of Urbanization on Solid Waste Pollution in the Current Urban Suburbs of Ha Noi: The Case of Hoai Duc District - Tuan, Nguyen Anh; Hiep, Tran Duc; Hang, Nguyen Thi Nguyet; Ngoc, Nguyen Minh; Lien, Pham Thi (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 1 No 3, 2021)
In recent years, solid waste pollution has been a burden on sustainable development in Vietnam. The suburban districts in major cities, in particular, have all witnessed a high rate of urbanization and a rapidly increasing amount of solid waste. Focusing on the case of unsustainably managed solid waste in Hoai Duc district (2016-2020), five research hypotheses, including factors affecting the increase of solid waste in Hoai Duc, are proposed, i.e.: Industrialization (based on the change of agricultural land area), population growth, urbanization (manifested by changes in urban land area), socio-economic policies, and educational qualification and public awareness of residents as well. It can be seen that population growth is just an indirect contributor to the situation, meanwhile, the sole cause of large daily plastic waste is none other than the burgeoning population attracted by urbanization. Therefore, the majority of attention and resources should be placed on strengthening policies that can keep urbanization under control, to ensure sustainable environmental development in addition to economic development.